2008
DOI: 10.2116/analsci.24.297
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Measurement of Circular Dichroism Spectra

Abstract: A microscope device to measure the circular dichroism (CD) spectra of a specified microscopic region of chiral samples was constructed by combining of a couple of objective lenses and a CCD camera, which was installed in a sample chamber of a commercially available CD spectropolarimeter. By using this apparatus, high quality micro-CD spectra in the 60 × 60 μm region of samples could be measured. Micro-CD spectra of thin film of chiral DNA samples on glass and a natural kidney bean leaf were measured, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In 2008, Watarai and collaborators described the first spatially resolved chiroptical investigation on samples of organic π-conjugated materials, i.e., drop-casted thin films of a cationic porphine/DNA complex, thanks to the development of a microscope able to collect the ECD spectrum of a microscopic area (60 × 60 μm 2 ), obtained by combining a couple of objective lenses with a CCD camera, installed in the sample chamber of a benchtop spectropolarimeter. 764 As previously described in section 3.3.4, freshly prepared spin-coated thin films of polyfluorene 80 exhibited a weak positive ECD band (g abs = +3.0 × 10 −4 at 400 nm), 684 attributable to a substantial CD iso arising from the supramolecular helical arrangement of individual π-conjugated chains, while after prolonged annealing in the liquid crystalline state, a strong negative ECD band appeared (g abs of about −0.15 at 403 nm), 683 attributable to a large LDLB contribution due to the rearrangement into helically overlapped layers of aligned polymer chains. Interestingly, in 2012, Finazzi and colleagues applied the two-photon fluorescence (TPF) scanning confocal microscopy for the ECD imaging investigation of thermally annealed spin-coated samples of 80, obtaining a 2D map of the transmission dissymmetry factor g (at 405 nm) associated with the ECD measured for transmitted light (Figure 76).…”
Section: Ecd In Thinmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, Watarai and collaborators described the first spatially resolved chiroptical investigation on samples of organic π-conjugated materials, i.e., drop-casted thin films of a cationic porphine/DNA complex, thanks to the development of a microscope able to collect the ECD spectrum of a microscopic area (60 × 60 μm 2 ), obtained by combining a couple of objective lenses with a CCD camera, installed in the sample chamber of a benchtop spectropolarimeter. 764 As previously described in section 3.3.4, freshly prepared spin-coated thin films of polyfluorene 80 exhibited a weak positive ECD band (g abs = +3.0 × 10 −4 at 400 nm), 684 attributable to a substantial CD iso arising from the supramolecular helical arrangement of individual π-conjugated chains, while after prolonged annealing in the liquid crystalline state, a strong negative ECD band appeared (g abs of about −0.15 at 403 nm), 683 attributable to a large LDLB contribution due to the rearrangement into helically overlapped layers of aligned polymer chains. Interestingly, in 2012, Finazzi and colleagues applied the two-photon fluorescence (TPF) scanning confocal microscopy for the ECD imaging investigation of thermally annealed spin-coated samples of 80, obtaining a 2D map of the transmission dissymmetry factor g (at 405 nm) associated with the ECD measured for transmitted light (Figure 76).…”
Section: Ecd In Thinmentioning
confidence: 99%
“…In 2008, Watarai and collaborators described the first spatially resolved chiroptical investigation on samples of organic π-conjugated materials, i.e., drop-casted thin films of a cationic porphine/DNA complex, thanks to the development of a microscope able to collect the ECD spectrum of a microscopic area (60 × 60 μm 2 ), obtained by combining a couple of objective lenses with a CCD camera, installed in the sample chamber of a benchtop spectropolarimeter …”
Section: Ecd Properties In Thin Films Of π-Conjugated Systems: Litera...mentioning
confidence: 99%
“…20 On the other hand extensive modifications to a commercial spectrometer (JASCO J-820) has recently allowed CD applications on solid samples (60 3 60 lm size) with CCD imaging of the selected sampling area. 21 …”
Section: Single Crystalsmentioning
confidence: 99%
“…In advance, the absorption spectra of ferrocene in bulk toluene solution and ferrocene aggregate were measured by microscope absorption spectroscopy. 50 Because the two spectra were essentially in agreement with each other, it was confirmed that there were no electronic interactions among ferrocene molecules in the solid aggregate. Therefore, we could consider the Faraday effect observed in the present study as the effect on the individual ferrocene molecules.…”
Section: Resultsmentioning
confidence: 71%